Role of Free Flaps in Facial Burn Reconstructions - Ravula, Parvathi; Reddy, D. Mukunda; Rangachari, Srikanth; Yerra, Kovida (Indian Journal of Plastic Surgery, 2024)
Traditionally, burn reconstructions have been performed by the use of skin grafting or local flaps. Recently free flaps are being used with increasing frequency. Although not very common in the head neck region, free flaps are mostly used for secondary reconstructions of cervicofacial contractures. We report the role of free flaps in postburn facial reconstructions, excluding neck and scalp burns. Sixteen free flaps used for postburn facial reconstructions were reviewed retrospectively, during the period between 2003 and 2023. The etiology, indications, timing, location, choice of the flap, type of reconstruction, and outcomes were analyzed. Indications and type of reconstructions were categorized to correlate with flap choice. The age of the patients ranged between 8 and 40 years. The etiology included electrical burns in six cases, flame burns in eight cases, and acid burns in two cases. Nine defects were in the central part of the face including the nose and the chin. Two primary and 14 secondary reconstructions were performed using free flaps from lateral thigh in 11 cases, lateral arm in 2 free flaps cases, radial forearm in 2 free flaps cases, and the posterior auricular flap in 1 case. There were no total flap failures. Secondary procedures were needed in 10 of 13 evaluable patients. Free flaps provide a good and safe option for selective postburn reconstructions in the face. The choice of flap mainly depends on the indication and type of reconstruction needed, apart from the availability of donor tissue and the surgeon's preference. Complex reconstructions may need larger and composite flaps to replace the components. Multiple secondary procedures are needed to achieve the objectives.
Keywords: facial burn scars; free flaps; loss of lip; scar nose; functional reconstruction